Contemporary Aquaculture Technologies : Fish Markets and Export - Armenia - International Finance Corporation (Washington, DC, 2017)
Fish farming has been carried out for centuries and is essentially fairly simple. It becomes a challenge when it is used for commerce. This brochure highlights the major complications associated with intensive and cost-efficient fish farming. In Armenia, there are a number of pro and cons to its relationship with fish farming. Armenia has abundant clean water sources. The water has limited suspended solids and little to no dissolved nitrogen. The effect of urbanization is also very limited, and water availability varies based on geographic location. However, Armenia’s geographical location presents a challenge. Feed, eggs, and equipment have to be imported, mainly from the United States (U.S.) and European Union (EU), which adds extra transportation costs that have significant impact especially on the cost of feed. To obtain a competitive farm gate price, several topics have to be addressed and are discussed in this report, along with common perspectives of fish farming.